Ischaemic events and stent thrombosis following planned discontinuation of study treatment with ticagrelor or clopidogrel in the PLATO study - Storey, Robert; Ardissino, Diego; Vignali, Luigi; Cairns, Richard; Becker, Richard C.; Cannon, Christopher P.; Mahaffey, Kenneth W.; Himmelmann, Anders; Katus, Hugo; James, Stefan K.; Wallentin, Lars; Investigators, on behalf of the PLATO (Thrombosis and haemostasis, 2018)
Thieme E-Books & E-Journals
Gesehen am 20.04.2020